Role of Polish cities in shaping attitudes of urban, educated youth towards European integration - Favero, Adrian Viktor (The University of Edinburgh, 2018)
Cities constitute important political, economic and cultural frameworks, playing a potentially crucial role in influencing the residents’ views and opinions about the world. In the context of Central Europe, there has been little attempt to examine the dynamics and construction of attitudes within urban societies. In this research, I explore the influence of urban spaces on citizens’ attitudes towards the city and the European Union (EU). This study investigates such citizen behaviours in the largest new EU member state - the Republic of Poland. Building on existing scholarship, I include economic factors and attachment-related approaches to assess support of EU integration among highly skilled citizens living in European cities, the so-called Eurostars. The thesis asks to what extent perceived conditions in Polish cities shape the attitudes of young well-educated urban citizens towards the EU. How do citizens’ perceptions of the local and of the supranational space affect their choice of location and work? I assess these questions by employing a sequential mixed methods approach that combines a quantitative and a qualitative method. I devised a survey that I conducted on 923 Masters (MA) students in Polish cities to evaluate their perceptions about their cities’ performance. The survey further assessed students’ attachments to their cities and their support for the EU. This collected data is complemented by detailed semi-structured interviews with 27 MA students to investigate whether their individual views on their respective city and on the EU influence their motivations to leave or stay in their city. This study situates these students as ‘potential Eurostars’ as they still live in their hometown. I conducted the comparative investigation in five large urban spaces in Poland: the Tricity area (Gdańsk-Sopot-Gdynia), Poznań, Warsaw, Wrocław and Kraków. Although not representative of every urban centre in Poland, these cities serve as a microcosm to understand the impact of local conditions and Europeanisation in Central and East Europe. (CEE) The use of cities as sites of analysis departs from the traditional and dominant nation-state framework. This thesis further underscores the attitudes of a specific social urban group, whose newly-gained access to the EU - with its opportunities for mobility - potentially offers them new perspectives. Such conditions may influence students’ choices of future location and work. The developed methodological framework, with its focus on Polish cities, can be further applied to other countries, groups and territorial units in future research. The quantitative and qualitative findings reveal a relatively marginal influence of urban conditions on place attachment. I further demonstrate that satisfaction with economic and cultural conditions in Polish cities relate to positive attitudes towards the EU. The perception of quality of life plays an important role for the sampled MA students in how they decide where to work and live after graduation. Although, attachment to the city does not necessarily lead to a negative opinion about the EU, it does impact students’ exit strategies and often leads to temporary migration plans. Other elements such as local patriotism, family and friends’ networks, equally shape this form of place attachment.
Keywords: European integration; Polish cities; quality of life; job opportunities; social networks; positive links